2016
DOI: 10.1097/pcc.0000000000000603
|View full text |Cite|
|
Sign up to set email alerts
|

Preferential Protection of Cerebral Autoregulation and Reduction of Hippocampal Necrosis With Norepinephrine After Traumatic Brain Injury in Female Piglets*

Abstract: Objective Traumatic brain injury (TBI) contributes to morbidity in children and boys are disproportionately represented. Cerebral autoregulation is impaired after TBI, contributing to poor outcome. Cerebral Perfusion Pressure (CPP) is often normalized by use of vasopressors to increase MAP. In prior studies, we observed that phenylephrine prevented in female but exacerbated impairment of autoregulation in male piglets after fluid percussion injury (FPI). In contrast, dopamine prevented impairment of autoregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 35 publications
(49 reference statements)
2
42
0
Order By: Relevance
“…In contrast, NE augmented ERK MAPK upregulation in newborn males but similarly blocked it in newborn females after TBI. 19 The magnitude of increase in CSF ERK MAPK was greater in newborn 19 compared with juvenile pigs (present study) after equivalent FPI. The ERK MAPK antagonist U 0126 permitted full restoration of hypotension induced pial artery dilation and THRR during carotid artery compression and maintained CBF after FPI similarly in male newborn 19 and juvenile pigs (present study).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In contrast, NE augmented ERK MAPK upregulation in newborn males but similarly blocked it in newborn females after TBI. 19 The magnitude of increase in CSF ERK MAPK was greater in newborn 19 compared with juvenile pigs (present study) after equivalent FPI. The ERK MAPK antagonist U 0126 permitted full restoration of hypotension induced pial artery dilation and THRR during carotid artery compression and maintained CBF after FPI similarly in male newborn 19 and juvenile pigs (present study).…”
Section: Discussionmentioning
confidence: 77%
“…In a recent prior study, it was observed that NE protected cerebral autoregulation and prevented hippocampal cell necrosis in newborn female but not newborn male piglets after TBI. 19 Taken together, the present study is the first to demonstrate that not only are there sex differences in outcome, but that there are age related differences in outcome when NE is used as part of the same critical care pathway for treatment of TBI. Because newborn and juvenile pigs may approximate the human neonate (6 months to 2 years old) and child (8 to 10 years old), respectively, 7 these data support the consideration of individualized medical approaches for younger and older children, in addition to that of boys compared with girls.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations